Quem bate na mulher machuca a família inteira: violência de gênero a partir de narrativas de uma família - Barros, Larissa Silva (2015)
This research is an focused study about how members of a family in a gender violence context tell their stories and how they mean the experienced violence in order to identify in their narratives values, traditions and practices which can stimulate or facilitate violence culture inside this family. This research also intended to analyze the intergenerational transmission process of gender violence and to discuss the construction of gender and relationships with violence in these family members. To this end, we interviewed, through the narrative interview technique, four members of a family in a gender violence context. For the children was added the use of recreational materials (modeling clay or puppets) to facilitate them to develop their narratives. The theoretical perspectives that framed this research were narrativist supported in studies of Jerome Bruner who proposes that the narrated stories give clues about the cultural rules that guide social interactions and how these are defined in terms of identity. The second approach used in this research stems from gender studies, emphasizing the relational database built from the psychosocial phenomena and negotiations through dialogues. It was observed from the narratives of the four family members, that each one of them told their own story revealing values, traditions and gender representations. The story took a place of justification of actions and management of self-image, especially for the parents, selecting facts and omitting others to preserve a positive self-image. Referring to the construction of gender, it can be said that they live conflicts of the passage of an old pattern of masculinity and femininity to a new more flexible and symmetrical configuration. Thus, these facts indicate that there was a variance of power where there is no static or deterministic relationship of subordination /domination by women, nor by man. Regarding the construction of gender in children, we found evidence that they rely dominant gender patterns and traditional masculinity and femininity roles constructed in the primary socialization process, especially in the family. It can be observed in the narratives that previous generations transmit practices and discourses in relation to masculine and feminine that can be meant in different ways. In the case of the mother, she has adhered to a position against submission and the father has not taken a stance to combat or avoid macho values. In fact, the father’s aggressive and rude hang contributes to the reproduction of traditional views about the male/female relation.